Natural History of Hazelnut Allergy and Current Approach to Its Diagnosis and Treatment - Arianna Giannetti; Alessandro Ruggi; Giampaolo Ricci; Giuliana Giannì; Carlo Caffarelli (Children, 2023)
Hazelnut allergy is the most prevalent type of nut allergy in Europe, with symptoms that can range from mild, such as hives and itching, to severe, such as anaphylaxis, particularly in patients who are sensitized to highly stable allergens, such as storage proteins. Compared to other types of food allergies, allergies to tree nuts, including hazelnuts, tend to persist throughout life. Although symptoms can appear in early childhood, they often continue into adulthood, with a minority of cases improving during adolescence. Currently, there is no curative treatment available for hazelnut allergy, and patients must adhere to a restrictive diet and carry autoinjective epinephrine. However, oral allergen immunotherapy (AIT) is a promising treatment option. Patients can be categorized based on their risk for severe reactions using various clinical, in vivo, and in vitro tests, including component-resolved diagnosis and oral food challenge. This review aims to provide an overview of the current knowledge of the natural history of hazelnut allergy and new approaches for its diagnosis and management.